An Early Examination of the Blue Ocean Strategy and Innovation Performance in Manufacturing Firms - Mohamed, Rapiah; Jamil, Che Zuriana Muhammad; Abd-Mutalib, Hafizah (International Journal of Supply Chain Management, 2020)
Business strategies are important for any firm, regardless of its size, to help them to stay competitive in the ever-changing business environment. Several popular strategic frameworks for the development of new business models have been proposed in the past decades. However, a new business model, known as the “blue ocean strategy”, has been rapidly gaining worldwide publicity and acceptance. The blue ocean strategy (BOS) is different from the traditional red ocean strategy, whereby BOS emphasises the need for firms to think and create innovation in their business to generate sustainable profits. In Malaysia, the government encourages organisations to implement BOS for the achievement of superior performance. This study examines the application of BOS in Malaysian manufacturing firms and its relationship with innovation performance. Data were collected using a questionnaire survey from respondents working in medium-sized manufacturing firms. The results revealed that the companies are applying this strategy to assist them in creating a competitive advantage. Furthermore, the findings indicate that there is a weak association between BOS and innovation performance. These findings contribute to the growing body of literature on BOS as well as assist entrepreneurs and policymakers in understanding the applicability of BOS in real businesses and the influence of business strategies on innovation performance.